Characterization of botryococcus sp. and identification of carbohydrates metabolic related enzymes toward lipid production - Abba, Zubainatu (2019)
The advancement of microalgal biofuels is faced with challenges among which is low strain performance in lipid production. Alternatively, the carbohydrate production in microalgal cells could be manipulated to increase the lipid content thereby maximizing the overall biofuel production. This work is aimed at determining metabolic pathway and enzymes involved in carbohydrate metabolism of Botryococcus sp. The B. sp. from Taman Negara Johor Endau Rompin was isolated and identified. Some relevant intracellular metabolites were extracted and quantified through HPLC and GC-MS analysis while extracellular metabolites excreted into the Bold basal medium were also analysed and identified through GC-MS. Enzymes involved in carbohydrate metabolism leading to lipid production in B. sp. under natural conditions were also identified through one-dimensional gel electrophoresis followed by proteomic mass spectrometry (LC-MS) and database searching. Finally, the carbohydrate to lipid metabolic pathway of B. sp. cultivated under natural conditions was determined. The total carbohydrate content was found to be 23 % per milligram biomass dry weight with monomeric sugars galactose, glucose, mannose, and arabinose. Total protein estimated for the microalgae B. sp. is 16.22 % and the lipid content was found to be 60.69 %. The extracellular metabolites constitute majorly cyclohydrocarbons, nitrogenated hydrocarbons, siloxanes, phenols and phenol derivatives. A glycolytic enzyme ‘Enolase ’which can generate phosphoenolpyruvate (PEP) and then convert it into pyruvate was identified in this study. Enolase which helps in high lipid metabolism was found in the cytoplasm and was used to construct the alternative pathway. Enolase was found to export fixed carbon (3PGA) to the cytoplasm, hence providing a shorter route to lipid production than the normal process via the plastid leading to the production of more lipid in Botryococcus.